Defect passivation material alkane ammonium salt and application

By designing the quaternary ammonium and primary amine salt structures of alkane ammonium salts, it is used for defect passivation of perovskite batteries, and the problem of poor stability of perovskite batteries under high humidity is solved, and the performance of the battery is significantly improved and stability, especially in high temperature and high humidity conditions, maintain high efficiency.

CN119263995APending Publication Date: 2025-01-07ZHEJIANG DASHENG NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411349057.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Perovskite solar cells have poor stability under room temperature conditions, resulting in attenuation of battery performance. The existing passivation materials are prone to deprotonation under high humidity, reducing the defect passivation ability of the material and battery performance.

Method used

A kind of alkane ammonium salt with a structure of quaternary ammonium salt and primary amine salt was designed, with C-C or C-O linear chains between the two amine groups. The primary amine salt side of the passivation material cooperated with the perovskite film layer bond. It is used with strong hydrophobicity and high stability at the ends of quaternary ammonium salts, and is used for defect passivation of perovskite batteries.

Benefits of technology

Improve the stability and performance of perovskite batteries, prevent decomposition into neutral amines and acids under high humidity, prolong the service life of the battery, and maintain 97% initial efficiency under 85℃ and 85% RH conditions. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263995A_ABST
    Figure CN119263995A_ABST
Patent Text Reader

Abstract

The invention discloses a defect passivation material alkane ammonium salt and application thereof, the structure of the ammonium salt is as follows: # imgabs0 #, R1, R2 and R3 are all H, R4, R5 and R6 are any one of-CH3,-CH2CH3,-C6H5 and other alkyl groups, X is any one of I-, Br-, Cl-, CH3COO-, HCOO-, PF6-and BF4-, a C-C straight chain or a C-O straight chain is arranged between two amino groups, the value range of n is 1-10, the quaternary ammonium salt end part of the ammonium salt is stable to water, the end part of the ammonium salt is stable to water, and the end part of the ammonium salt is stable to water. Even if water vapor exists, the compound cannot be decomposed into corresponding neutral amine, acid and the like, and when the compound is applied to a perovskite battery, the performance and the stability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to an alkane ammonium salt of a defect passivation material and an application thereof. Background Art

[0002] Since perovskite materials are hygroscopic, the absorbed water causes the stability of perovskite solar materials to be poor at room temperature, which further leads to the attenuation of battery performance. This is one of the reasons why perovskite solar cells show obvious efficiency attenuation after long-term operation, which seriously hinders commercial applications.

[0003] In response to the above problems, some companies in the market have developed passivation materials with the goal of improving the stability of perovskite batteries. Currently commonly used passivation materials, such as the two-terminal ammonium salt structure (N atom connected to 3 hydrogen atoms), will deprotonate in the presence of water vapor to generate corresponding neutral amines and acids, reducing the defect passivation ability of the material, thereby reducing the performance and stability of the device.

[0004] If all hydrogen atoms at both ends of the passivation material are replaced with alkyl groups, since the nitrogen atoms at both ends of the passivation material are not connected to active hydrogen atoms, deprotonation will not occur even under high humidity conditions, which improves the stability of the passivation material itself. At the same time, since the nitrogen atoms are all connected to alkyl groups, they are hydrophobic and can isolate moisture from the perovskite, thereby improving the stability of the perovskite battery. However, compared with the ammonium salt with the terminal nitrogen atom connected to the hydrogen atom, the ammonium salt with the terminal nitrogen atom connected to the alkyl group has a large steric hindrance, so it is similar to [PbI6] 2- The weak bonding of the octahedron leads to a decrease in its passivation performance, which reduces the performance of the battery and needs to be improved. Summary of the invention

[0005] To solve at least one of the above technical defects, the present invention provides the following technical solutions:

[0006] The first aspect of the present application document discloses a defect passivation material, an alkane ammonium salt, whose structure is as follows:

[0007]

[0008] Wherein R1, R2, R3 are all H, R4, R5, R6 are any of -CH3, -CH2CH3, -C6H5 and other alkyl groups, X is I - Br - , Cl - 、CH3COO - HCOO - PF6 - 、BF4 - Any of the above, the two amine groups are a CC straight chain or a CO straight chain, and the value range of n is 1-10.

[0009] Further, the ammonium salt is any one of the following structural formulas:

[0010]

[0011] When used, if one end of the ammonium salt is a quaternary ammonium salt type (here, the N atom is connected to four alkyl groups) and the other end is a primary amine salt type (here, the N atom is connected to three hydrogen atoms and one alkyl group), the primary amine salt side of the passivation material has a strong bonding effect with the perovskite film layer, and the quaternary ammonium salt end is highly hydrophobic and stable.

[0012] The second aspect of the present application discloses the application of the above-mentioned ammonium salt in perovskite batteries, such as directly mixing it in the corresponding components to form an integral film layer, or coating the ammonium salt on the corresponding film layer and curing it into a film.

[0013] Preferably, the perovskite cell is of single junction type or stacked type.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The present invention designs the structure of ammonium salt, which has a small molecular weight and an amphiphilic configuration. The main chain is a straight chain and at least one end is a quaternary ammonium salt. The quaternary ammonium salt end is stable to water and will not decompose into corresponding neutral amines and acids even in the presence of water vapor. When applied to perovskite batteries, it helps to improve the performance and stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 It is a schematic diagram of the synthesis route.

[0018] Figure 2 This is a stability comparison chart of perovskite / heterojunction stacked cells. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0020] For the synthesis of ammonium salt, the following synthesis method is used:

[0021] Take one equivalent of N,N-dimethylethylenediamine and place it in dimethyl ether solution. Add ten equivalents of methyl iodide and six equivalents of K2CO3 respectively under stirring at room temperature. Continue stirring for 3 hours, add an appropriate amount of dichloromethane to dissolve the precipitated ammonium salt, filter out excess carbonate, concentrate the filtrate in vacuo, wash with ether, filter, and vacuum dry to obtain the desired ammonium salt.

[0022] Or, in a flask, add one equivalent of N,N-dimethylethylenediamine, appropriate amounts of dichloromethane and tetrahydrofuran, then add 1.05 equivalents of Boc anhydride, stir at room temperature for two hours, then dilute with ethyl acetate, then wash with 1M HCl and brine, dry the organic phase with MgSO4, remove the organic solvent in vacuo and dry. Next, take one equivalent of Boc-protected N,N-dimethylethylenediamine and place it in a dimethyl ether solution, add ten equivalents of iodomethane and six equivalents of K2CO3 respectively while stirring at room temperature, continue stirring for 3 hours, add an appropriate amount of dichloromethane to dissolve the precipitated ammonium salt, filter out excess carbonate, concentrate the filtrate in vacuo, wash with ether, filter, and dry in vacuo. Finally, take one equivalent of Boc-protected quaternary ammonium salt, then add one equivalent of HI solution, stir at room temperature for four hours, then precipitate the iodine salt with ether, and dry in vacuo to obtain the desired ammonium salt. The synthetic route is as follows: Figure 1 shown.

[0023] According to the above synthesis route, the ammonium salt with the following structural formula can be obtained by replacing ethylenediamine containing a corresponding number of carbon atoms, specifically:

[0024]

[0025] The application of the above ammonium salt in perovskite batteries is as follows:

[0026] The preparation method of single-junction perovskite cell is as follows:

[0027] (1) FTO conductive glass with a specification of 1.5×1.5 cm is obtained by laser cutting and set aside.

[0028] (2) Preparation of nickel oxide hole transport layer

[0029] A nickel oxide ethanol dispersion with a concentration of 20 g / mL was prepared, and the dispersion was spin-coated on the conductive surface of the FTO conductive glass at a rotation speed of 2000 rpm for 30 seconds, and annealed at 100° C. for 10 minutes to obtain a laminated structure of FTO / nickel oxide layer.

[0030] (3) Preparation of 2-PACZ hole transport layer

[0031] A 1 g / mL [2-(9H-carbazole-9-yl)ethyl]phosphoric acid (2-PACz) isopropanol dispersion was prepared and spin-coated on the surface of the nickel oxide layer away from the FTO conductive glass at a rotation speed of 3000 rpm for 30 seconds, and annealed at 100°C for 10 minutes to obtain a stacked structure of FTO / nickel oxide layer / 2-PACZ layer.

[0032] (4) Preparation of lead salt film

[0033] The 6×6 cm FTO / nickel oxide layer / 2-PACZ layer stacked structure prepared in step (3) was transferred to a vacuum evaporation device, and lead iodide and cesium iodide were used as evaporation sources. A lead salt film was deposited on the 2-PACZ surface at 1×10-5 Pa and 450°C to obtain a FTO / nickel oxide layer / 2-PACZ layer / Cs0.05Pb2.05 layer stacked structure, which was used as the base film layer A for standby use.

[0034] (5) Preparation of perovskite active layer

[0035] Prepare an isopropanol dispersion of FAI (formamidine hydroiodide), MACl (methylammonium chloride) and a mixture of any of the above ammonium salts, wherein the concentration of FAI is 80 mg / mL, the concentration of MACl is 6 mg / mL, and the concentration of the ammonium salt is 1 mg / mL, drop it on the above substrate, spin coat it at a speed of 3000 rpm / s for 30 seconds, and then anneal it at 150°C for 15 minutes to obtain a perovskite active layer.

[0036] (6) C60, BCP and Ag are deposited on FTO / nickel oxide layer / 2-PACZ layer / perovskite layer at the same time to obtain a perovskite cell, whose structure is FTO / nickel oxide layer / 2-PACZ layer / perovskite layer / C60 / BCP / Ag.

[0037] The preparation method of perovskite / heterojunction stacked solar cell is as follows:

[0038] (1) n-type <100> A polished Cz silicon wafer (size 210mm×210mm) substrate with a crystal orientation is placed in a PECVD system, and a layer of 5nm thick intrinsic hydrogenated amorphous silicon is deposited on the front and back sides of the silicon wafer to obtain intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon.

[0039] (2) PECVD-plasma enhanced chemical vapor deposition (PECVD) is used on one surface of the above-mentioned stacked structure to deposit p-type doped amorphous silicon with a thickness of 15 nm to obtain p-type doped amorphous silicon / intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon.

[0040] (3) On the other side surface of the stacked structure obtained in step (2), a 15 nm thick n-type doped nano-silicon oxide layer is deposited by PECVD to obtain a p-type doped amorphous silicon / intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon / n-type doped nano-silicon oxide layer.

[0041] (4) Depositing indium tin oxide on both sides of the stacked structure prepared in step (3) by magnetron sputtering to obtain indium tin oxide (88 nm thick) / p-type doped amorphous silicon / intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon / n-type doped nano-silicon oxide layer / indium tin oxide (15 nm thick).

[0042] (5) Atomic layer deposition is used to deposit nickel oxide with a thickness of 5 nm on one side of the indium tin oxide with a thickness of 15 nm in the stacked structure prepared in step (4), and then a solution spin coating method is used to prepare an atomic layer thickness 2-PACZ layer to obtain indium tin oxide / p-type doped amorphous silicon / intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon / n-type doped nano-silicon oxide layer / indium tin oxide / nickel oxide / 2-PACZ.

[0043] (6) Preparation of lead salt and cesium salt films:

[0044] The stacked structure obtained in step (5) is transferred to a vacuum evaporation device, and lead iodide, lead bromide and cesium iodide are used as evaporation sources. A Cs0.2PbI1.4Br0.8 layer (thickness 250nm) is deposited on the surface of 2-PACZ under vacuum conditions of 1×10-6Pa and 400°C to obtain an indium tin oxide / p-type doped amorphous silicon / intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon / n-type doped nano-silicon oxide layer / indium tin oxide / nickel oxide / 2-PACZ / Cs0.2PbI1.4Br0.8 layer as a base film layer for later use.

[0045] (7) Preparation of perovskite active layer:

[0046] An isopropanol dispersion containing 50 mg / mL FAI, 30 mg / mL MAI (methyl ammonium iodide) and 10 mg / mL MACl was prepared, dropped on the above substrate, spin-coated at a speed of 3000 rpm for 30 seconds, and then annealed at 150°C for 15 minutes to obtain a perovskite active layer, obtaining indium tin oxide / p-type doped amorphous silicon / intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon / n-type doped nano-silicon oxide layer / indium tin oxide / nickel oxide / 2-PACZ / perovskite layer.

[0047] (8) 1 mg / mL ammonium salt and isopropanol dispersion was added dropwise onto the substrate, spin coated at 3000 rpm for 30 seconds, and then annealed at 150°C for 15 minutes.

[0048] (9) Preparation of electron transport layer, barrier layer and metal electrode.

[0049] On the passivation layer, 20nm C60 was deposited by thermal evaporation, 20nm SnO2 was deposited by ALD-atomic layer deposition, 50nm ITO was deposited by magnetron sputtering, and 2um silver paste was screen-printed on both sides to obtain a perovskite / heterojunction stacked cell. Its structure is Ag / indium tin oxide / p-type doped amorphous silicon / intrinsic hydrogenated amorphous silicon / n-type crystalline silicon / intrinsic hydrogenated amorphous silicon / n-type doped nano-silicon oxide layer / indium tin oxide / nickel oxide / 2-PACZ / perovskite layer / Example 1 / C60 / SnO2 / ITO / Ag.

[0050] Of course, when the above ammonium salt is applied to the battery, it can be formed into a film layer alone, and formed into an interface defect passivation film layer at a position away from the substrate. The above ammonium salt can also be mixed with an organic salt as an additive in the organic salt.

[0051] Taking the perovskite / heterojunction stacked cell as an example, the preparation step (7) is different from the above preparation steps. Specifically, in step (7), the preparation of the perovskite active layer is to prepare 50 mg / mL FAI, 30 mg / mL MAI, 10 mg / mL MACl and 1 mg / mL of any of the above structure ammonium salts, drop them on the above substrate, spin coat at a speed of 3000 rpm for 30 seconds, and then anneal at 150°C for 15 minutes to obtain the perovskite active layer.

[0052] Example 1

[0053] Perovskite / heterojunction stacked cells (passivation film type) are prepared using the above method, and the structural formula of the ammonium salt is as follows:

[0054]

[0055] Example 2

[0056] Perovskite / heterojunction stacked cells (passivation film type) are prepared using the above method, and the structural formula of the ammonium salt is as follows:

[0057]

[0058] Comparative Example 1

[0059] Perovskite / heterojunction stacked cell (passivation film type), the preparation method is consistent with Example 1, and the structural formula of the ammonium salt is as follows:

[0060]

[0061] Comparative Example 2

[0062] Perovskite / heterojunction stacked cell (passivation film type), the preparation method is consistent with Example 1, and the structural formula of the ammonium salt is as follows:

[0063]

[0064] The performance of the battery prepared above was tested, wherein the aging condition in the battery stability test was: 85°C / 85%RH, and the specific data are shown in Table 1. Figure 2 As shown:

[0065] Table 1

[0066] Voc(V) <![CDATA[Jsc(mA cm -2 )]]> FF PCE(%) Example 1 1.92 19.1 0.81 29.70 Example 2 1.91 19.2 0.8 29.34 Comparative Example 1 1.89 19.1 0.78 28.15 Comparative Example 2 1.85 18.9 0.75 26.22

[0067] It can be seen from Table 1 that the perovskite / heterojunction stacked cells containing the ammonium salt of this scheme have excellent performance in open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF), and power conversion efficiency (PCE).

[0068] Attached Figure 2 It can be seen that after the packaged battery has been aged for 1000 hours at 85°C and 85% humidity, the perovskite / heterojunction stacked battery based on the passivation material shown in Example 1 retains 97% of its initial efficiency, and its stability is much higher than that of Comparative Example 1 (83%), and is comparable to that of Comparative Example 2.

[0069] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A defect passivation material, an alkane ammonium salt, characterized in that: Its structure is as follows: Wherein R1, R2, and R3 are all H, R4, R5, and R6 are any of -CH3, -CH2CH3, and -C6H5 alkyl groups, and X is I - Br - , Cl - 、CH3COO - HCOO - PF6 - 、BF4 - Any of the above, the two amine groups are a CC straight chain or a CO straight chain, and the value range of n is 1-10.

2. The defect passivation material of claim 1, wherein: The ammonium salt is any one of the following structural formulas:

3. Use of the ammonium salt according to any one of claims 1 to 2 in perovskite batteries.

4. The use according to claim 3, characterized in that: The perovskite cell is of single junction type or stacked type.

Citation Information

Cited By

  • Deuterium-labeled (2-aminoethyl) trimethyl ammonium chloride and synthesis method thereof

    CN121248422A